Number 22 Internment Camp: German Prisoners of War and Canadian Internment Operations in Mimico, Ontario, 1940-1944 - Goodlet, Kirk (Ontario History, 2012)
This article investigates the development of internment operations at Camp M in Mimico, Ontario, from 1940 to 1944. Using a variety of archival sources, this study sheds light on one of the only camps built near a major Canadian city during the Second World War, and one that remains recondite to most Canadians. From its inception Camp M suffered from a series of administrative, organizational, and personnel issues, which exacerbated operations. This was compounded by severe infrastructure problems that led to its expeditious closing in July 1944. Today both provincial and federal governments are constructing a 1,650-person “superjail” on the very site that once housed over 500 German POWs. This article, therefore, serves to inform further discussion about the past and present utility of the site.